A taxonomic study of the genus Longchuanacris Zheng et Fu (Orthoptera: Acrididae: Catantopinae), with descriptions of two new species from Yunnan, China - Mao, Ben-Yong; Niu, Yao; Ou, Xiao-Hong; Zheng, Zhe-Min; Scott, Matthew B. (Zootaxa, 2011)
All types of Longchuanacris Zheng et Fu, 1989 are examined. Longchuanacris guangxiensis Zheng et Ren, 2007 is synonymized with Caryanda neoelegans Otte, D. 1995, and Longchuanacris bilobata Mao, Ren et Ou, 2007 is synonymized with L. macrofurcula Zheng et Fu, 1989; seventy three topotypes are designated for L. macrofurcula. Longchuanacris lobata Niu et Ou, sp. nov. and L. microfurcula Niu et Zheng, sp. nov. are described as new species. Six Longchuanacris species are keyed and their distributions are stated. These species are distributed in southwestern Yunnan, China. Type specimens are deposited in the Faculty of Conservation Biology, Southwest Forestry University (SWFU), Yunnan Province, China and in the Institute of Zoology, Chinese Academy of Sciences, Beijing, China (IZCAS).